INVESTIGATION ON THE COMPARATIVE PROXIMATE AND ELEMENTAL COMPOSITIONS OF THE FRUIT AND LEAF OF SOLANUM AETHIOPICUM CULTIVATED IN JOS - Achuenu, Chukuka; Emesi, I. C.; Dashe, Raymond; Edah, Alexander O.; Mshelia, Suleman Stephen (FUDMA JOURNAL OF SCIENCES, 2024)
Solanum aethiopicum, commonly referred to as the African eggplant, is one of the commonly consumed vegetables in Nigeria and other African countries because of its nutritional value and health benefits. Despite its pervasiveness, limited studies have focused on the proximate and elemental compositions of this species, especially in Jos, Nigeria. The study conducted a comprehensive proximate and elemental analysis of the fruit and leaf extracts of S. aethiopicum using n-hexane, acetone, and ethanol for maceration. Proximate and elemental analyses were conducted on fruit and leaf extracts of Solanum aethiopicum, using n-hexane, acetone, and ethanol for maceration. The results showed that fruit extracts had higher moisture, crude fat, fiber, and total protein compared to leaf extracts. However, leaf extracts had slightly higher total carbohydrates and total ash. Specifically, the moisture content for n-hexane fruit extract was 61.04 ± 0.47, while for leaf extract was 59.75 ± 0.64. Total protein in n-hexane fruit extract was 1.74 ± 0.04 compared to 1.55 ± 0.25 in leaf extract. Fiber content was 5.57 ± 0.11 in fruit and 3.54 ± 0.04 in leaf extracts. Crude fat was 5.70 ± 0.45 in fruit and 6.23 ± 0.13 in leaf extracts. Total carbohydrates was 10.24 ± 0.37 in fruit and 11.40 ± 0.09 in leaf extracts, while total ash was 15.71 ± 1.24 in fruit and 17.52 ± 1.17 in leaf extracts. Elemental analyses revealed that magnesium (Mg) was 183.06 ± 2.56 in fruit and 165.60 ± 0.29 in leaf extracts; iron (Fe) was 68.17 ± 0.28...